Multicore C++ Standard Template Library in a Generative Way - Szűgyi, Zalán; Török, Márk; Pataki, Norbert (Electronic notes in theoretical computer science, 2011)
Nowadays, the one of the most important challenges in the programming is the efficient usage of multicore processors. Many new programming languages and libraries support multicore programming. Cilk++ is one of the most well-known languages extension of C++ providing new keywords for multicore programming. C++ Standard Template Library is efficient generic library but it does not support parallelism. It is optimized to the sequential realm, hence it can be an efficiency bottleneck when it is used in multicore environment. In this paper we argue for a multicore implementation of C++ Standard Template Library for Cilk++. We consider the implementation of containers, algorithms, and functors as well. Our implementation takes advantage of generative technologies of C++. We also measure the speedup of our implementation.